2010
DOI: 10.1037/a0018626
|View full text |Cite
|
Sign up to set email alerts
|

The effects of majority versus minority source status on persuasion: A self-validation analysis.

Abstract: The present research proposes that sources in the numerical majority (vs. minority) can affect persuasion by influencing the confidence with which people hold their thoughts in response to the persuasive message. Participants received a persuasive message composed of either strong or weak arguments that was presented by a majority or a minority source. Consistent with the self-validation hypothesis, we predicted and found that the majority (vs. minority) status of the source increased the confidence with which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 80 publications
4
37
0
2
Order By: Relevance
“…One notable direction would be to examine how other variables may also be capable of producing contentdependent self-validation effects. First, along with high credibility, several other source characteristics have been shown to initiate self-validation in persuasion; including high efficacy (Clark, Evans, & Wegener, 2011), attractiveness , and representing a majority viewpoint (Horcajo, Petty, & Briñol, 2010). It stands to reason that differences in evaluative focus could influence self-validation with respect to these characteristics and produce effects that have not been documented in the literature.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…One notable direction would be to examine how other variables may also be capable of producing contentdependent self-validation effects. First, along with high credibility, several other source characteristics have been shown to initiate self-validation in persuasion; including high efficacy (Clark, Evans, & Wegener, 2011), attractiveness , and representing a majority viewpoint (Horcajo, Petty, & Briñol, 2010). It stands to reason that differences in evaluative focus could influence self-validation with respect to these characteristics and produce effects that have not been documented in the literature.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…As noted, previous research on source status and self-validation 140 (Horcajo et al, 2010) showed that majority source status can increase the confidence with which recipients held their thoughts compared to minority source status. When the thoughts were positive (in response to strong arguments), majority source status was associated with more persuasion than minority source status because people relied more on their 145 positive thoughts generated in response to the convincing message.…”
mentioning
confidence: 84%
“…XML Template (2012) [9.11.2012-4:23pm] [1-17] //blrnas3/cenpro/ApplicationFiles/Journals/TandF/3B2/PSIF/Vol00000/120045/APPFile/TF-PSIF120045.3d (PSIF) [INVALID Specifically, Horcajo, Petty, and Brin˜ol (2010) demonstrated that the placement of source status information is an important moderating factor in 80 the domain of attitude change. Specifically, the timing of source status information (prior to vs after message processing) is relevant to understanding the different effects and multiple processes that can produce attitude change, as well as the potential consequences for attitude strength resulting from those multiple processes (for an illustration applied to source 85 credibility, see, Tormala, Brin˜ol, & Petty, 2007).…”
mentioning
confidence: 99%
“…En este caso, una variable persuasiva ya no afectará las actitudes a través de un proceso relacionado a la generación de pensamientos, sino a uno vinculado a la metacognición, como, por ejemplo, la validez que se le otorgan a los propios pensamientos (Petty, Briñol & Tormala, 2002). Ejemplos de variables que pueden actuar a través de uno u otro proceso, dependiendo del momento de presentación, son el rol que posee el poder del receptor (de entregar recompensas y castigos; Briñol, Petty, Valle, Rucker & Becerra, 2007), el rol de la afirmación de la identidad del receptor (Briñol, Petty, Gallardo & DeMarree, 2007), el rol de la credibilidad que posee la fuente de información (Tormala, Briñol & Petty, 2006), el rol de la mayoría o minoría numérica (Horcajo, Petty & Briñol, 2010), entre otros. En el contexto del estudio de PRs, solo Howard (1990) ha controlado experimentalmente el momento en que se presentaba una PR, mostrando que estas afectaban a las actitudes, sobre todo cuando se entregaban después de un mensaje.…”
Section: Algunas Limitaciones En El Estudio De Las Prs En Psicología unclassified